LOCAL GOVERNMENT STRATEGY IN SOLVING THE CONFLICT OF LAND TRADITIONAL GROUNDS IN BUKIT KERMAN DISTRICT, KERINCI REGENCY - Darminto, Citra; Haryadi, Haryadi; Hasalena, Leni (JISPO Jurnal Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to determine the causes of conflicts and the Kerinci Regency government’s strategy in conflict resolution. This study uses a qualitative descriptive method with data collection techniques such as observation, interviews and documentation. The main cause of conflict between Pulau Sangkar Village and Kebun Baru Village was due to lack of agricultural land, and unclear boundaries between villages. The strategy of the regional government in resolving conflicts is through mediation between the two conflicting parties so that a letter of agreement is formed between Kebun Baru Village and Pulau Sangkar Village so that the conflict does not recur.